Climatic conditions cause complex patterns of covariation between demographic traits in a long‐lived raptor. (10th December 2014) - Herfindal, Ivar; van de Pol, Martijn; Nielsen, Jan T.; Sæther, Bernt‐Erik; Møller, Anders P.
Summary: Environmental variation can induce life‐history changes that can last over a large part of the lifetime of an organism. If multiple demographic traits are affected, expected changes in climate may influence environmental covariances among traits in a complex manner. Thus, examining the consequences of environmental fluctuations requires that individual information at multiple life stages is available, which is particularly challenging in long‐lived species. Here, we analyse how variation in climatic conditions occurring in the year of hatching of female goshawks Accipiter gentilis (L.) affects age‐specific variation in demographic traits and lifetime reproductive success (LRS). LRS decreased with increasing temperature in April in the year of hatching, due to lower breeding frequency and shorter reproductive life span. In contrast, the probability for a female to successfully breed was higher in years with a warm April, but lower LRS of the offspring in these years generated a negative covariance among fecundity rates among generations. The mechanism by which climatic conditions generated cohort effects was likely through influencing the quality of the breeding segment of the population in a given year, as the proportion of pigeons in the diet during the breeding period was positively related to annual and LRS, and the diet of adult females that hatched in warm years contained fewer pigeons. Climatic conditions experienced during different stages of individual life histories caused complex patterns of environmental covariance among demographic traits even across generations. Such environmental covariances may either buffer or amplify impacts of climate change on population growth, emphasizing the importance of considering demographic changes during the complete life history of individuals when predicting the effect of climatic change on population dynamics of long‐lived species. Abstract : This article demonstrates how climate early in life can have long‐lasting effects on lifetime fitness of goshawks. Climate also had short‐term effects on reproductive performance, and these effects were in the opposite direction compared to the long‐term effects. This causes negative co‐variations between the immediate and delayed responses to climate.